Genetic variation, structure and dispersal among Cape buffalo populations from the Hluhluwe-Imfolozi and Kruger National Parks of South Africa - Bastos, Armanda D.S. (University of Pretoria, 2013)
Thesis (PhD (Zoology))--University of Pretoria, 2007.